Shopping Behavior for ADHD Drugs: Results of a Cohort Study in a Pharmacy Database - Cepeda, M. Soledad (Springer International Publishing, 2014)
OBJECTIVE: Attention-deficit hyperactivity disorder (ADHD) medications are subject to abuse, misuse, and diversion. Obtaining ADHD prescriptions from multiple prescribers or filled across multiple pharmacies, known as ‘doctor shopping’, may reflect such unsanctioned use. We sought to create a definition of shopping behavior that differentiated ADHD medications from medications with low risk of diversion, i.e. asthma medications, and describe the incidence, frequency, and demography of shopping behavior. METHODS: This was a retrospective cohort study in a pharmacy database—LRx—covering 65 % of US retail pharmacies. Subjects had ADHD or asthma medication dispensed between February 2011 and January 2012. We followed subjects for 18 months to assess the number with overlapping dispensings from different prescribers, and the number of prescribers and pharmacies involved in those dispensings. RESULTS: We included 4,402,464 subjects who were dispensed ADHD medications, and 6,128,025 subjects who were dispensed asthma medications. Overlapping prescriptions from two or more prescribers dispensed by three or more pharmacies was four times more frequent in the ADHD cohort than in the asthma cohort. Using this definition, ADHD medication shopping behavior was more common among experienced users than naïve users, and was most common in subjects aged 10–39 years. Among subjects who shopped, 57.4 % shopped only once (accounting for 22.4 % of episodes), and 9.2 % shopped six or more times (accounting for 42.0 % of episodes). Shoppers more often received stimulant ADHD drugs than non-stimulants. CONCLUSIONS: Overlapping prescriptions by different prescribers and filled at three or more pharmacies defines ADHD medication shopping. Shopping behavior is most common in adolescents and younger adults. A small proportion of shoppers is responsible for a large number of shopping episodes.